2005
DOI: 10.1007/s00234-004-1324-x
|View full text |Cite
|
Sign up to set email alerts
|

Fourier analysis of intracranial aneurysms: towards an objective and quantitative evaluation of the shape of aneurysms

Abstract: Shape irregularities of intracranial aneurysms may indicate an increased risk of rupture. To quantify morphological differences, Fourier analysis of the shape of intracranial aneurysms was introduced. We compared the morphology of 45 unruptured (UIA) and 46 ruptured intracranial aneurysms (RIA) in 70 consecutive patients on the basis of 3D-rotational angiography. Fourier analysis, coefficient of roundness and qualitative shape assessment were determined for each aneurysm. Morphometric analysis revealed signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 26 publications
0
25
1
Order By: Relevance
“…Some of the first morphological indexes, such as non-sphericity, ellipticity, and undulation were proposed by Raghavan et al 16 and studied further in subsequent studies. 4,9 Rohde et al 17 applied Fourier analysis to capture the shape irregularities of intracranial aneurysms. Their Fourier analysis was performed on 2D data sets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the first morphological indexes, such as non-sphericity, ellipticity, and undulation were proposed by Raghavan et al 16 and studied further in subsequent studies. 4,9 Rohde et al 17 applied Fourier analysis to capture the shape irregularities of intracranial aneurysms. Their Fourier analysis was performed on 2D data sets.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we introduce a series of original shape descriptors based on the writhe number. 6 Similar to recent morphological studies, 9,12,13,16,17 the rupture status prediction is performed on a data set of aneurysms, which were labeled as being ruptured or not at the time of detection by the treating neurosurgeons. In the proposed methodology, aneurysms are isolated from the segmented vasculature represented as a 3D triangular mesh.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Recently, a large-cohort prospective study found that unruptured aneurysms with a daughter sac (an irregular protrusion of the wall of the aneurysm) are more likely to rupture than aneurysms with a regular shape.…”
Section: Irregular Wall and Ar Of Symmetric Bilateral Aneurysms Predimentioning
confidence: 99%
“…The aim of Rohde's research and analysis was to identify whether those aneurysms were lobular or daughter aneurysms. Up until that date conventional angiography was insufficient to make this differentiation (19). Dhar et al performed a detailed analysis of the morphometric ratios of the aneurysm and this particular type of procedure was previously not possible with conventional angiography (8).…”
Section: Nikolic I Et Al: Morphometric Parameters For Rupture Of Intmentioning
confidence: 99%
“…Thanks to the well-developed software and the rotational angiography they were able to work on the assessment of irregularities to identify whether it is in a lobus or a daughter aneurysm. Conventional angiography is insufficent to show this difference (19).…”
Section: Aspect Ratio (Ar)mentioning
confidence: 99%